Decree No. 111/2000 amending certain provisions of the executive statutes of Law No. 120/1982 on reorganization of trade agency works and certain trade brokerage / middlemen's works and the executive statutes of Law No. 121/1982 concerning the register of importers. (2025)
Seria No. 11/2000